The relationship between spiritual and political worldview in political education - Nassimov, М.Ө.; Paridinova, Б.Ж. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2025)
The proposed problem is being studied for the first time in domestic political science. The article comprehensively analyzes the relationship between spiritual and political worldviews in political education. In the context of modern globalization, the intersection of spiritual and political views directly affects the internal system of human beliefs, their political activity, and civic responsibility. The authors substantiate the need to develop the interaction of spiritual values ​​and political ideas in an integrative key in the process of political education. The article discusses the essence of spirituality, the structure of the political worldview, the role of the institution of the family, and the importance of educational policy in shaping the worldview of students. The harmony of political and spiritual worldviews is achieved through the introduction of ideological components into curricula, advanced training of teachers, and the organization of critical dialogue. The results of the study provide specific recommendations for improving the content of education in higher education institutions, increasing the socio-political activity of future specialists, and the formation of democratic values. The article not only demonstrates the theoretical foundations of the interaction of spiritual and political worldviews but also contributes to the modernization of the practice of political education.